Mediation of Brand Image Between the Influence of Social Media Marketing and Electronic Word of Mouth on Purchase Intention Somethinc - Febriani Putri, Annisa; Darta Hadi, Effed (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the effect of social media marketing and electronic word-of-mouth on purchase intention, considering the role of brand image as a mediator. Using a non-probability sampling method with a purposive sampling approach involving 273 respondents. The collected data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) using Smart PLS software. The results showed that social media marketing and electronic word-of-mouth significantly influence purchase intention. Social media marketing through brand image significantly influences consumers' purchase intention. However, electronic word of mouth does not significantly affect brand image, and brand image does not significantly mediate the relationship between electronic word of mouth and purchase intention.